2020
DOI: 10.3892/ol.2020.11809
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA GAS5 in human cancer (Review)

Abstract: Long non-coding RNAs (lncRNAs) constitute a group of >200-nucleotide ncRNA molecules. lncRNAs regulate several cell functions, such as proliferation, apoptosis, invasion and metastasis. Meanwhile, lncRNAs are abnormally expressed in human malignancies, where they suppress or promote tumor growth. The present study focused on growth arrest-specific transcript 5 (GAS5), a well-known lncRNA that acts as a tumor suppressor but is suppressed in multiple types of cancer, including mammary carcinoma, prostate cancer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 77 publications
(121 reference statements)
2
55
0
Order By: Relevance
“…Studies have found that lncRNA expression may be functionally associated with drug resistance in acute leukemias [ 68 , 80 , 89 , 104 ]. For example, the lncRNA growth arrest-specific transcript 5 (GAS5) is downregulated in many cancers and may be used as a potential marker of treatment response in remission induction therapy for children with ALL [ 81 , 82 , 105 ].…”
Section: Long Non-coding Rnas In Progenitor B-cell Acute Lymphoblamentioning
confidence: 99%
“…Studies have found that lncRNA expression may be functionally associated with drug resistance in acute leukemias [ 68 , 80 , 89 , 104 ]. For example, the lncRNA growth arrest-specific transcript 5 (GAS5) is downregulated in many cancers and may be used as a potential marker of treatment response in remission induction therapy for children with ALL [ 81 , 82 , 105 ].…”
Section: Long Non-coding Rnas In Progenitor B-cell Acute Lymphoblamentioning
confidence: 99%
“…On the other hand, in the long-term perspective, metabolic disorders could be reflected in premature events, and be marked on the genome as methylated genes, as for example in infancy. These findings indicate that GAS5 manifests multifaceted roles in various physiological processes, including tumor ontogenesis [ 19 ]. GAS5 acts as a gene regulatory element through three basic modes of action.…”
Section: The Long Non-coding Rna Repressor Gas5mentioning
confidence: 99%
“…Studies have found that lncRNA expression may be functionally associated with drug resistance in acute leukemias [68,80,89,104]. For example, the lncRNA growth arrest-specific transcript 5 (GAS5) is downregulated in many cancers and may be used as a potential marker of treatment response in remission induction therapy for children with ALL [81,82,105].…”
Section: Notable Case: Lncrna Gas5 and Its Connection To Glucocorticomentioning
confidence: 99%